Iatrogenic fracture of the maxillary tuberosity - a case report - Anna Olborska; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2017)
The article presents a case of an iatrogenic maxillary tuberosity fracture due to poor actions of the dentist during an attempt of extracting upper third molar.